Implementation of Criminal Action Prosecution Online in Realizing Principle of Fast Prosecution, Simple & Low Cost - Ardito Yudho Pratomo; Umar Ma'ruf; Aryani Witasari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
Indonesia is a state of law, thus everything is regulated by law, if there are people who violate the law then it is resolved through a judicial process. The Covid-19 virus has had an impact on the need for online trials. The formulation of the problem in this study is how the implementation and constraints of the implementation of the stages of prosecuting criminal cases (online) and how the ideal implementation in the application of the stage of prosecuting criminal cases (online) in order to realize the principles of fast, simple and low-cost justice in Indonesia. Wonogiri Prosecutor's Office? This study uses empirical legal research methods. The results of this study indicate that the implementation of the stages of prosecuting criminal cases (online) in order to realize the principles of fast, simple and low-cost justice at the Wonogiri Prosecutor's Office is carried out with Supreme Court Regulation (PERMA) No. 1 of 2019 concerning Administration and Trial in Courts Electronically. Implementation constraints in the application of (online) prosecution of criminal cases due to legal factors, Cultural Community facilities and infrastructure. The ideal implementation of the application of online criminal prosecution in order to realize the principles of fast, simple and low-cost justice at the Wonogiri Prosecutor's Office requires clear arrangements, human resources who have IT skills. Internet Network, a good understanding of the law intensively conduct outreach to the community.